Neuroprotective Effects of Quercetin on Ischemic Stroke: A Literature Review - Zhang, Leilei; Ma, Jingying; Yang, Fan; Li, Sishi; Ma, Wangran; Chang, Xiang; Yang, Lin (Frontiers in Pharmacology, 2022)
Ischemic stroke (IS) is characterized by high recurrence and disability; however, its therapies are very limited. As one of the effective methods of treating acute attacks of IS, intravenous thrombolysis has a clear time window. Quercetin, a flavonoid widely found in vegetables and fruits, inhibits immune cells from secreting inflammatory cytokines, thereby reducing platelet aggregation and limiting inflammatory thrombosis. In pre-clinical studies, it has been shown to exhibit neuroprotective effects in patients with ischemic brain injury. However, its specific mechanism of action remains unknown. Therefore, this review aims to use published data to elucidate the potential value of quercetin in patients with ischemic brain injury. This article also reviews the plant sources, pharmacological effects, and metabolic processes of quercetin in vivo, thus focusing on its mechanism in inhibiting immune cell activation and inflammatory thrombosis as well as promoting neuroprotection against ischemic brain injury.